Plant diversity and ecosystem services of wetland based agroforestry system in Tripura, Northeast India - Taran, Moitree; Deb, Sourabh (Indian Journal of Agroforestry, 2019)
Wetland based agroforestry system is one of the prevalent systems of Tripura, Northeast India having rich plant and animal diversity and provides various services to the mankind. Present study represents a pioneering work on ecosystem services of wetland based agroforestry system. In the study, tree carbon stock was calculated by allometric equation and valuation of ecosystem services was done by questionnaire based survey following standard methodology. Total 39 species belonging to 24 families were identified from wetland based agroforestry systems with dominating species of Mangifera indica (IVI=47.24), Artocarpus heterophyllus (IVI=37.86) and Anacardium occidentale (IVI=20.43). High tree carbon stock (60.46 t ha-1) was observed in the system as compared to other agricultural systems because people practice aquaculture mainly with tree species. This system provides different provisional services viz., food, fuelwood, timber, medicine, fodder, livestock and aquaculture. Protection of nature, education, recreational and aesthetic value are different cultural services provided by wetland based agroforestry system. Total revenue earned from different ecosystem services (provisional and cultural) were Rs. 1,18,484/household/year. The study proves the high productivity as well as the potentiality of wetland based agroforestry system. So, this system should be conserved and managed for the maintenance of biological diversity and human wellbeing.